Exploring the Art Potential of Elementary Teachers: Sponge Painting Workshop - Tangsi Tangsi; Siti Asmaulul Izmi; Dwi Wahyuni Hamka; Jusbaeni Jusbaeni; Sri Riski Wulandari (PT. Global Research Collaboration, 2024)
This community service focuses on improving the competence of Pao-Pao State Elementary School teachers in implementing sponge media as an art teaching aid. Through focused training, teachers were intensively trained to master sponge painting techniques and understand the significance of art in the learning process. The evaluation results showed a significant improvement in teachers' ability to create innovative and interesting artworks. Thus, it is expected to stimulate students' creativity and make art learning more fun and interactive. The importance of continuous training in developing the quality of art education at the primary school level is also emphasised in this study. The training not only provides direct benefits for the teachers, but also has a positive impact on the students' learning process and ultimately, on improving the overall quality of education.